Altered Spatial Distribution of the Diastolic Left Ventricular Pressure Difference in Heart Failure - Iwano, Hiroyuki; Kamimura, Daisuke; Fox, Ervin; Hall, Michael; Vlachos, Pavlos; Little, William C. (Journal of the American Society of Echocardiography, 2015)
The left ventricle fills in early diastole because of a progressive intraventricular pressure difference (IVPD) that extends from the left atrium to the left ventricular (LV). The aim of this study was to test the hypothesis that in patients with symptomatic heart failure (HF) regardless of LV ejection fraction (EF), an increase in left atrial (LA) pressure maintains early diastolic filling because of a preserved IVPD from the left atrium to the mid left ventricle, while the IVPD from the mid left ventricle to the apex is diminished because of reduced LV suction. One hundred fifty-one patients with HF (50 with HF with preserved EF [HFpEF; EF ≥ 50%] and 101 with HF with reduced EF [HFrEF; EF < 50%]) and 28 normal controls were prospectively enrolled. The IVPDs from the left atrium to the LV apex (total IVPD), the left atrium to the mid left ventricle (basilar IVPD), and the mid left ventricle to the apex (apical IVPD) were determined using color M-mode Doppler echocardiographic data to integrate the Euler equation. The propagation of early diastolic filling was also assessed by color M-mode Doppler. The mean LV EF was 0.63 ± 0.07 in patients with HFpEF, 0.32 ± 0.09 in those with HFrEF, and 0.64 ± 0.06 in controls. Peak early diastolic transmitral flow velocities (E) were similar among the groups, and basilar IVPDs were maintained in the HFpEF and HFrEF groups (HFpEF, 1.59 ± 0.62 mm Hg; HFrEF, 1.49 ± 0.75 mm Hg; controls, 1.80 ± 0.61 mm Hg; P = NS, analysis of variance). However, apical IVPDs were decreased in both HF groups (HFpEF, 1.18 ± 0.56 mm Hg [P < .01 vs controls]; HFrEF, 0.87 ± 0.48 mm Hg [P < .01 vs controls]; controls, 1.65 ± 0.62 mm Hg), resulting in decreased total IVPDs in patients with HF (HFpEF, 2.55 ± 0.80 mm Hg [P < .01 vs controls]; HFrEF, 2.16 ± 0.80 mm Hg [P < .01 vs controls]; controls, 3.17 ± 0.91 mm Hg). E/e′ ratios were increased in patients with HF, consistent with elevated LA pressure. In patients with HF, E was correlated with basilar IVPD but not with apical IVPD, whereas propagation of the filling was correlated with the apical IVPD but not with the basilar IVPD. In patients with HFpEF and those with HFrEF, apical IVPDs were reduced while basilar IVPDs were maintained by elevated LA pressure, resulting in preserved E.